FEMINISM IN JUNG CHANG’S WILD SWANS - Machfud Muhammad Sodiq (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2023)
This study is about feminism in Jung Chang’ Wild Swans. The feminism is identified by the character of a woman who has been triggered by the social injustice at that time such as corruption, people humiliation, cultural abolishment, discrimination, private life interference and victims all of which are done by the previous and late government. Using close reading method and feminism as the approach, the researcher can identify the words and actions of the main character that belong to feminism. Finally the researcher finds that the main character, the woman, belongs to the feminism in her speeches and actions identified by the way the woman’s donation to economies and societies, elimination of sexual aspiration from the female presence to get a more serious, earnest equivalence with men, and women acquisition of equal rights; the first refers to struggling for the elimination of those who belong to other party, existences as follows: teachers, private life, children, husband, and her own existence. The second refers to woman’s right to choose her husband and the last refers to the wife’s right to have her husband’s care.